Lithium supplementing composite layer and preparation method thereof, lithium supplementing method, pre-lithiated negative pole piece, secondary battery and electronic device

By using a lithium-enhancing composite layer, including a gel electrolyte layer, a lithium-enhancing layer and a support layer, the problems of low efficiency and poor cycle life of the negative electrode sheet of the lithium-ion battery are solved for the first time, and a higher energy density is achieved.

CN119920902APending Publication Date: 2025-05-02NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510111675.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The first time the Coulombic efficiency and poor cycle life of the negative electrode sheet of existing lithium-ion batteries is low, resulting in the energy density being unable to meet the ever-increasing needs.

Method used

A lithium supplementation composite layer is adopted, including a gel electrolyte layer, a lithium supplement layer and a support layer. By regulating the ionic conductivity and surface density of the gel electrolyte layer, a fast and uniform lithium supplement process is achieved.

Benefits of technology

It improves the first Coulomb efficiency of lithium-ion batteries, reduces the cycle capacity attenuation, and increases the battery's energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920902A_ABST
    Figure CN119920902A_ABST
Patent Text Reader

Abstract

The invention provides a lithium supplementing composite layer and a preparation method thereof, a lithium supplementing method, a pre-lithiated negative pole piece, a secondary battery and an electronic device, the lithium supplementing composite layer comprises a gel state electrolyte layer, a lithium supplementing layer and a supporting layer which are stacked, the lithium supplementing layer is arranged between the gel state electrolyte layer and the supporting layer, the gel-state electrolyte layer comprises a lithium salt, a solvent and a polymer, and the lithium supplementing layer comprises lithium metal and / or lithium alloy. The lithium supplement composite layer meets the above characteristics, lithium supplement is carried out on the negative pole piece, the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation is reduced, and the energy density of the secondary battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a lithium replenishing composite layer and a preparation method thereof, a lithium replenishing method, a pre-lithiated negative electrode plate, a secondary battery and an electronic device. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high power, and long cycle life. They are widely used in consumer electronics, electric bicycles, and electric vehicles. As their application scope continues to expand, the energy density and cycle performance requirements of lithium-ion batteries continue to increase. The current common lithium-ion battery negative electrode graphite materials can no longer meet the requirements for energy density. Although silicon-carbon and silicon-oxygen negative electrode materials have high theoretical specific capacity and are ideal materials for replacing negative electrode graphite materials and improving the energy density of lithium-ion batteries, they have not been widely used due to their low first coulomb efficiency and poor cycle life. The existing method to improve the first coulomb efficiency and reduce cycle attenuation of silicon-carbon or silicon-oxygen negative electrodes is to pre-replenish lithium to the negative electrode plate to supplement the irreversible capacity consumed during the first charge, discharge, and cycle, improve the first coulomb efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrodes, and then improve the energy density of lithium-ion batteries.

[0003] The existing methods of replenishing lithium in negative electrode sheets mainly include replenishing lithium with lithium powder, replenishing lithium with lithium strips by rolling, and replenishing lithium with electrochemical methods. Replenishing lithium with lithium powder means that lithium powder is adsorbed on the surface of the negative electrode sheet under the action of vibration and electric field, and then rolled to compact the lithium powder to the surface of the negative electrode sheet to prevent it from falling off, thereby replenishing lithium in the negative electrode sheet. Lithium powder is easy to float and has high environmental requirements; lithium powder is flammable and poses a great safety hazard to operators; lithium powder has a large particle size (Dv50 of lithium powder is about 25μm), and it is easy to replenish lithium unevenly at low lithium replenishment amounts; the lithium pressing layer has low adhesion and is difficult to use on a large scale. Replenishing lithium with lithium strips by rolling means that the lithium strip is passed through a rolling roller and a composite roller for rolling so that the lithium strip adheres to the composite roller, and then the lithium strip on the surface of the composite roller is transferred to the surface of the negative electrode sheet to obtain a replenished lithium negative electrode sheet. Lithium strip rolling lithium replenishment is usually carried out by mechanically rolling the lithium strip onto the negative electrode sheet. As the existing process is difficult to produce thinner metal lithium strips, the amount of lithium that the negative electrode sheet can absorb is far less than the amount of lithium provided by the metal lithium strip, resulting in excessive lithium replenishment. After the metal lithium strip is pressed onto the surface of the negative electrode sheet, heat is generated, causing safety risks. In addition, the utilization rate of the lithium film covered is low. The lithium film that has not been converted into lithium ions loses its electronic conductivity and becomes "dead lithium", thereby hindering the diffusion of lithium ions, causing the internal resistance of the lithium-ion battery to increase and polarization to increase. More seriously, the unconverted lithium promotes the nucleation of lithium ions, resulting in lithium precipitation and causing safety problems. Electrochemical lithium replenishment refers to assembling lithium foil or lithium alloy with a diaphragm, a negative electrode sheet, and an electrolyte into a stack, then chemically forming the stack, and then drying the formed negative electrode sheet to form a lithium replenished negative electrode sheet. Electrochemical lithium replenishment uses stacked lithium replenishment or belt-type lithium replenishment, which has low lithium replenishment efficiency, high cost, and is difficult to promote industrialization. It can be seen that the above three lithium replenishment methods have certain problems in environmental control, lithium replenishment uniformity, lithium replenishment amount control, lithium replenishment efficiency, and side reactions after lithium replenishment. Therefore, it is urgent to provide a lithium replenishment method that has high lithium replenishment uniformity and high lithium replenishment efficiency, can improve the first coulombic efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrodes, reduce cycle capacity attenuation, and improve the energy density of lithium-ion batteries. Summary of the invention

[0004] The purpose of this application is to provide a lithium replenishing composite layer and its preparation method, a lithium replenishing method, a pre-lithiated negative electrode plate, a secondary battery and an electronic device, so as to improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. The specific technical scheme is as follows:

[0005] The first aspect of the present application provides a lithium-replenishing composite layer, wherein the lithium-replenishing composite layer comprises a stacked gel electrolyte layer, a lithium-replenishing layer and a support layer, the lithium-replenishing layer is arranged between the gel electrolyte layer and the support layer, the gel electrolyte layer comprises a lithium salt, a solvent and a polymer, and the lithium-replenishing layer comprises lithium metal and / or a lithium alloy. The lithium-replenishing composite layer satisfies the above characteristics, and replenishing lithium to the negative electrode plate can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0006] In one embodiment of the present application, the ionic conductivity σ of the gel electrolyte layer is 0.1mS / cm to 15mS / cm. By regulating the ionic conductivity of the gel electrolyte layer within the scope of the present application, the gel electrolyte layer has a suitable ionic conductivity, the ion conductivity of the gel electrolyte layer is relatively high, the gel electrolyte layer is in contact with the negative electrode material layer, the lithium replenishing layer and the negative electrode material layer form an internal short circuit, the lithium atoms in the lithium replenishing layer undergo an oxidation reaction to lose electrons to generate lithium ions, the electrons and lithium ions are more quickly transferred to the surface or inside of the negative electrode material layer through the gel electrolyte layer, the electrons and lithium ions undergo a reduction reaction in the negative electrode material layer to form a lithium intercalation compound, which can replenish lithium more quickly and further increase the amount of lithium replenishment, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0007] In one embodiment of the present application, the lithium salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(oxalatoborate) or lithium oxalatodifluoroborate. The above lithium salts are selected to make the gel electrolyte layer have a suitable ionic conductivity, and electrons and lithium ions can be transferred to the surface or the inside of the negative electrode material layer through the gel electrolyte layer more quickly, so that lithium can be replenished more quickly and the amount of lithium replenishment can be further increased, thereby further improving the initial coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0008] In one embodiment of the present application, the solvent includes at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, N,N-dimethylformamide, N-methylpyrrolidone, dioxolane, 1-butyl-3-methylimidazolium bromide or ethylene glycol dimethyl ether. The above solvents are used to facilitate the dissociation of lithium salts, enable the gel electrolyte layer to have a suitable ionic conductivity, enable electrons and lithium ions to be more quickly transferred to the surface or interior of the negative electrode material layer through the gel electrolyte layer, enable faster lithium replenishment, further increase the amount of lithium replenishment, thereby further improving the initial coulomb efficiency of the secondary battery, further reducing the cycle capacity decay, and further improving the energy density of the secondary battery.

[0009] In one embodiment of the present application, the polymer includes at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer or polyethylene glycol dimethacrylate. The above polymers can be selected to obtain an electrolyte system with excellent mechanical properties, high ion conductivity and good compatibility, and the gel electrolyte layer can have a suitable ion conductivity, and electrons and lithium ions can be transferred to the surface or inside of the negative electrode material layer more quickly through the gel electrolyte layer, so that lithium can be replenished more quickly and the amount of lithium replenishment can be further increased, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0010] In one embodiment of the present application, the surface density CW of the gel electrolyte layer is 1 g / m 2 Up to 100g / m 2 Preferably, the surface density CW of the gel electrolyte layer is 2 g / m 2 Up to 40g / m 2 By regulating the surface density of the gel electrolyte layer within the scope of this application, the gel electrolyte layer can be made more continuous, and the uniformity of lithium replenishment can be improved; and the lithium ion transmission distance can be made moderate, which is beneficial to increase the amount of lithium ions passing through per unit time, and is beneficial to increase the lithium replenishment rate and amount, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0011] The second aspect of the present application provides a method for preparing a lithium supplement composite layer in any of the aforementioned embodiments, which comprises the following steps:

[0012] (1) coating a lithium metal powder slurry on a support layer, drying it, and rolling it to form a lithium supplement layer; or rolling a lithium foil and / or a lithium alloy foil onto a support layer to form a lithium supplement layer; or coating a lithium or lithium alloy molten slurry on a support layer, cooling it, and rolling it to form a lithium supplement layer; wherein the rolling pressure P1 is 0.1T / 10mm to 2T / 10mm;

[0013] (2) mixing a lithium salt, a solvent, and a polymer to obtain a gel electrolyte; coating the gel electrolyte on the surface of the lithium replenishing layer to form a gel electrolyte layer, thereby obtaining a lithium replenishing composite layer.

[0014] The lithium-replenishing composite layer is prepared by the preparation method of the lithium-replenishing composite layer provided in the present application. The lithium-replenishing composite layer includes a gel electrolyte layer, a lithium-replenishing layer and a supporting layer arranged in a stacked manner. The composition of the gel electrolyte layer and the type of the lithium-replenishing layer are within the scope of the present application. The gel electrolyte layer has a suitable ionic conductivity. The gel electrolyte layer in the lithium-replenishing composite layer contacts the negative electrode material layer. The lithium-replenishing layer and the negative electrode material layer form an internal short circuit. The lithium atoms in the lithium-replenishing layer undergo an oxidation reaction to lose electrons to generate lithium ions. The electrons and lithium ions are transferred to the surface or the inside of the negative electrode material layer through the gel electrolyte layer. The electrons and lithium ions undergo a reduction reaction in the negative electrode material layer to form a lithium-insertion compound, thereby realizing the pre-lithiation process of the negative electrode material layer. Since a gel electrolyte layer is provided between the lithium-replenishing layer and the negative electrode material layer, the possibility of introducing impurities into the lithium-replenishing layer is small. In addition, the above-mentioned pre-lithiation process can quickly replenish lithium and increase the amount of lithium replenishment. At the same time, the interface bonding pressure, bonding time, and bonding temperature are controlled to achieve controllable lithium replenishment, which can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. The support layer can provide better support for the lithium replenishment layer and the gel electrolyte layer, and improve the mechanical strength of the lithium replenishment composite layer, so that the lithium replenishment composite layer can be peeled off from the surface of the negative electrode material layer more smoothly after lithium replenishment, reducing the possibility of fracture of the lithium replenishment composite layer, which is beneficial to the lithium replenishment of the negative electrode plate.

[0015] In one embodiment of the present application, the concentration C of the lithium salt in the gel electrolyte is Li 0.2mol / L to 2mol / L; Based on the mass of the gel electrolyte layer, the mass percentage of the polymer W P 1% to 30%. By regulating the concentration of lithium salt and the mass percentage of polymer within the scope of this application, it is beneficial to obtain an electrolyte system with excellent mechanical properties, high ion conductivity and good compatibility, so that the gel electrolyte layer can have a suitable ion conductivity, and electrons and lithium ions can be transferred to the surface or inside of the negative electrode material layer through the gel electrolyte layer more quickly, so that lithium can be replenished more quickly and the amount of lithium replenishment can be further increased, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0016] In one embodiment of the present application, the viscosity η of the gel electrolyte is 30000 mPa·s to 200000 mPa·s. By regulating the viscosity of the gel electrolyte within the scope of the present application, the gel electrolyte has a suitable viscosity, which is beneficial for coating the gel electrolyte on the surface of the lithium supplementation layer and is beneficial for processing performance.

[0017] The third aspect of the present application provides a lithium supplementation method, which comprises the following steps:

[0018] The negative electrode sheet is dried, and the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The lithium supplement composite layer prepared by the preparation method in any of the above embodiments and the negative electrode sheet are laminated so that the gel electrolyte layer contacts the negative electrode material layer, and a pre-lithiation treatment is performed, the lamination pressure P2 of the gel electrolyte layer and the negative electrode material layer is 0.1MPa to 0.6MPa, the lamination time t2 of the gel electrolyte layer and the negative electrode material layer is 0.01h to 1h, and the lamination temperature T2 of the gel electrolyte layer and the negative electrode material layer is 25°C to 90°C. After the pre-lithiation treatment is completed, the lithium supplement composite layer and the negative electrode sheet are peeled off to form a pre-lithiation negative electrode sheet.

[0019] The lithium replenishment method provided in the present application is used to prepare a pre-lithiated negative electrode plate, which is beneficial to quickly replenish lithium to the negative electrode plate and increase the amount of lithium replenished in the negative electrode plate. The obtained pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0020] The fourth aspect of the present application provides a pre-lithiated negative electrode plate, which is obtained by the lithium supplementation method in any of the above embodiments. The pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0021] The fifth aspect of the present application provides a secondary battery, the secondary battery comprising the pre-lithiated negative electrode plate in any of the above embodiments. Therefore, the secondary battery of the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.

[0022] The sixth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.

[0023] Beneficial effects of this application:

[0024] The present application provides a lithium replenishing composite layer and a preparation method thereof, a lithium replenishing method, a pre-lithiated negative electrode plate, a secondary battery and an electronic device, wherein the lithium replenishing composite layer comprises a stacked gel electrolyte layer, a lithium replenishing layer and a supporting layer, wherein the lithium replenishing layer is arranged between the gel electrolyte layer and the supporting layer, the gel electrolyte layer comprises a lithium salt, a solvent and a polymer, and the lithium replenishing layer comprises lithium metal and / or a lithium alloy. The lithium replenishing composite layer satisfies the above characteristics, and replenishing lithium to the negative electrode plate can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0025] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0027] Figure 1 A schematic diagram of the structure of a lithium-replenishing composite layer according to an embodiment of the present application;

[0028] Figure 2 This is a schematic diagram of the structure of the negative electrode plate and the lithium supplement composite layer during the pre-lithiation process of an implementation scheme of the present application. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0030] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0031] The first aspect of the present application provides a lithium supplement composite layer, wherein the lithium supplement composite layer comprises a stacked gel electrolyte layer, a lithium supplement layer and a support layer, wherein the lithium supplement layer is arranged between the gel electrolyte layer and the support layer. Figure 1 As shown, the lithium supplement composite layer 10 includes a gel electrolyte layer 13, a lithium supplement layer 12 and a support layer 11, which are stacked, and the lithium supplement layer 12 is arranged between the gel electrolyte layer 13 and the support layer 11. The gel electrolyte layer includes a lithium salt, a solvent and a polymer, and the lithium supplement layer includes lithium metal and / or a lithium alloy. The above-mentioned lithium alloy may include but is not limited to a lithium aluminum alloy.

[0032] The inventors have found that the gel electrolyte layer includes lithium salt, solvent and polymer, and the gel electrolyte layer has suitable ion conductivity. The gel electrolyte layer in the lithium supplement composite layer is in contact with the negative electrode material layer. Figure 2As shown, the gel electrolyte layer 13 is brought into contact with the negative electrode material layer 15 disposed on the two surfaces of the negative electrode current collector 14, the lithium replenishing layer and the negative electrode material layer form an internal short circuit, the lithium atoms in the lithium replenishing layer undergo an oxidation reaction to lose electrons to generate lithium ions, the electrons and lithium ions are transferred to the surface or the inside of the negative electrode material layer through the gel electrolyte layer, and the electrons and lithium ions undergo a reduction reaction in the negative electrode material layer to form a lithium intercalation compound, thereby realizing the pre-lithiation process of the negative electrode material layer. Since a gel electrolyte layer is disposed between the lithium replenishing layer and the negative electrode material layer, the possibility of introducing impurities into the lithium replenishing layer is small. Moreover, the above-mentioned pre-lithiation process can replenish lithium quickly and increase the amount of lithium replenishment. At the same time, the interface bonding pressure, bonding time, and bonding temperature are controlled to achieve controllable lithium replenishment, which can improve the initial coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. After the pre-lithiation treatment is completed, the lithium replenishing composite layer is peeled off from the negative electrode plate. The lithium replenishing composite layer includes a supporting layer. The supporting layer can provide better support for the lithium replenishing layer and the gel electrolyte layer, thereby improving the mechanical strength of the lithium replenishing composite layer, so that the lithium replenishing composite layer can be peeled off from the surface of the negative electrode material layer more smoothly after lithium replenishment, reducing the possibility of fracture of the lithium replenishing composite layer, which is beneficial to the lithium replenishment of the negative electrode plate.

[0033] In one embodiment of the present application, the ionic conductivity σ of the gel electrolyte layer is 0.1mS / cm to 15mS / cm. Exemplarily, the value of σ can be 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or a range consisting of any two of the above values. By regulating the ionic conductivity of the gel electrolyte layer within the scope of the present application, the gel electrolyte layer has a suitable ionic conductivity, the ion conductivity of the gel electrolyte layer is relatively high, the gel electrolyte layer is in contact with the negative electrode material layer, the lithium replenishment layer and the negative electrode material layer form an internal short circuit, the lithium atoms in the lithium replenishment layer undergo an oxidation reaction to lose electrons to generate lithium ions, the electrons and lithium ions are more quickly transferred to the surface or the inside of the negative electrode material layer through the gel electrolyte layer, the electrons and lithium ions undergo a reduction reaction in the negative electrode material layer to form a lithium intercalation compound, which can replenish lithium more quickly and further increase the amount of lithium replenishment, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery. The present application does not particularly limit the method of regulating the ionic conductivity of the gel electrolyte layer, as long as the purpose of the present application can be achieved. For example, the ionic conductivity of the gel electrolyte layer can be regulated by regulating the ionic conductivity of the gel electrolyte. Exemplarily, the ionic conductivity of the gel electrolyte can be regulated by regulating the amount of lithium salt added and the degree of dissociation of the lithium salt in the solvent. For example, with the addition of lithium salt, the initial lithium salt content is low, the degree of dissociation of the lithium salt in the solvent remains unchanged, and the ionic conductivity of the gel electrolyte increases; with the increase in the amount of lithium salt added, the degree of dissociation of the lithium salt in the solvent decreases, and the ionic conductivity of the gel electrolyte first increases and then decreases.

[0034] In one embodiment of the present application, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate, lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(oxalatoborate) (LiBOB) or lithium oxalatodifluoroborate (LiDFOB). The above lithium salts are selected to make the gel electrolyte layer have a suitable ionic conductivity, and electrons and lithium ions can be transferred to the surface or the inside of the negative electrode material layer through the gel electrolyte layer more quickly, so that lithium can be replenished more quickly and the amount of lithium replenishment can be further increased, thereby further improving the initial coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0035] In one embodiment of the present application, the solvent includes at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propylene carbonate (PC), N,N-dimethylformamide, N-methylpyrrolidone, dioxolane, 1-butyl-3-methylimidazolium bromide or ethylene glycol dimethyl ether. The above solvents are selected to facilitate the dissociation of lithium salts, enable the gel electrolyte layer to have a suitable ionic conductivity, enable electrons and lithium ions to be more quickly transferred to the surface or interior of the negative electrode material layer through the gel electrolyte layer, enable faster lithium replenishment, further increase the amount of lithium replenishment, thereby further improving the initial coulomb efficiency of the secondary battery, further reducing the cycle capacity decay, and further improving the energy density of the secondary battery.

[0036] In one embodiment of the present application, the solvent comprises ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate. Based on the total volume of the solvent, the volume percentage of ethylene carbonate is 20% to 50%, the volume percentage of dimethyl carbonate is 20% to 50%, the volume percentage of ethyl methyl carbonate is 0% to 30%, and the volume percentage of diethyl carbonate is 0% to 30%.

[0037] In one embodiment of the present application, the polymer includes at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer or polyethylene glycol dimethacrylate. The above polymers can be selected to obtain an electrolyte system with excellent mechanical properties, high ion conductivity and good compatibility, and the gel electrolyte layer can have a suitable ion conductivity, and electrons and lithium ions can be transferred to the surface or inside of the negative electrode material layer more quickly through the gel electrolyte layer, so that lithium can be replenished more quickly and the amount of lithium replenishment can be further increased, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0038] In one embodiment of the present application, the surface density CW of the gel electrolyte layer is 1 g / m 2 Up to 100g / m 2 Preferably, the surface density CW of the gel electrolyte layer is 2 g / m 2 Up to 40g / m 2. Exemplarily, the value of CW can be 1, 2, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 or a range consisting of any two of the above values. By regulating the surface density of the gel electrolyte layer within the scope of this application, the gel electrolyte layer can be made more continuous and the uniformity of lithium replenishment can be improved; and the lithium ion transmission distance can be moderate, which is beneficial to increase the amount of lithium ions passing through per unit time, and is beneficial to increase the lithium replenishment rate and amount, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery. The present application does not particularly limit the method of regulating the surface density of the gel electrolyte layer, as long as the purpose of the present application can be achieved. For example, the surface density of the gel electrolyte layer can be regulated by regulating the coating amount of the gel electrolyte. Exemplarily, when the gel electrolyte is coated on the surface of the lithium replenishment layer, the coating amount of the gel electrolyte is increased to increase the surface density of the gel electrolyte layer; the coating amount of the gel electrolyte is reduced to reduce the surface density of the gel electrolyte layer.

[0039] In one embodiment of the present application, the thickness H1 of the gel electrolyte layer is 0.5 μm to 50 μm, preferably, the thickness H1 of the gel electrolyte layer is 1 μm to 20 μm. Exemplarily, the value of H1 can be 0.5, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range consisting of any two of the above values. By regulating the thickness of the gel electrolyte layer within the scope of the present application, the gel electrolyte layer has a suitable thickness, the transmission distance of electrons and lithium ions is moderate, and the electrons and lithium ions can effectively recombine to form lithium-inserted compounds, which is beneficial to improve the lithium replenishment rate and amount, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0040] In one embodiment of the present application, the thickness H2 of the lithium replenishment layer is 0.001mm to 1mm, and preferably, the thickness of the lithium replenishment layer is 0.005mm to 0.1mm. Exemplarily, the value of H2 can be 0.001, 0.003, 0.005, 0.007, 0.009, 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.3, 0.5, 0.7, 0.9, 1 or a range consisting of any two of the above values. By regulating the thickness of the lithium replenishment layer within the scope of the present application, the lithium replenishment layer has a suitable thickness, and the lithium replenishment layer can provide a suitable number of lithium atoms, which is beneficial to increase the amount of lithium replenishment in the negative electrode material layer, and can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.

[0041] In one embodiment of the present application, the thickness H3 of the support layer is 3 μm to 50 μm, preferably, the thickness H3 of the support layer is 5 μm to 20 μm. By adjusting the thickness of the support layer within the scope of the present application, the support layer has a suitable thickness, which can better meet the need of peeling the lithium-replenishing composite layer from the surface of the negative electrode material layer after lithium replenishment, which is conducive to further replenishing lithium to the negative electrode plate, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0042] In one embodiment of the present application, the support layer includes at least one of metal foil, polyethylene terephthalate film, polypropylene film, polyethylene film or polyimide film, and the metal foil includes copper foil, nickel foil, steel foil or copper-nickel alloy foil. By selecting the above support layer, better support can be provided for the lithium replenishment layer and the gel electrolyte layer, and the mechanical strength of the lithium replenishment composite layer can be further improved, so that the lithium replenishment composite layer can be more smoothly peeled off from the surface of the negative electrode material layer after lithium replenishment, and the possibility of fracture of the lithium replenishment composite layer can be reduced, which is conducive to further replenishing lithium to the negative electrode plate, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0043] In one embodiment of the present application, along the running direction of the lithium-replenishing composite layer, that is, the MD direction, the tensile strength K3 of the support layer is 1.5N / 10mm to 200N / 10mm, preferably, the tensile strength K3 of the support layer is 22N / 10mm to 100N / 10mm. Along the running direction of the lithium-replenishing composite layer, the tensile strength of the support layer is within the scope of the present application, the lithium-replenishing composite layer has a high mechanical strength, and can better meet the need of peeling the lithium-replenishing composite layer from the surface of the negative electrode material layer after lithium replenishment, which is conducive to further replenishing lithium to the negative electrode plate, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.

[0044] The second aspect of the present application provides a method for preparing a lithium supplement composite layer in any of the aforementioned embodiments, which comprises the following steps:

[0045] (1) Under the condition of ambient temperature ≤30°C and humidity ≤1.7%, a lithium metal powder slurry is applied to a support layer and dried and rolled to form a lithium supplement layer; or a lithium foil and / or a lithium alloy foil is rolled to a support layer to form a lithium supplement layer; or a lithium or lithium alloy molten slurry is applied to a support layer and cooled and rolled to form a lithium supplement layer; wherein the roller pressure P1 is 0.1T / 10mm to 2T / 10mm; specifically, the roller pressure P11 of rolling after applying the lithium metal powder slurry to the support layer is 0.1T / 10mm to 2T / 10mm; the roller pressure P12 of rolling after the lithium foil and / or the lithium alloy foil is rolled to the support layer is 0.1T / 10mm to 2T / 10mm; the roller pressure P13 of rolling after applying the lithium or lithium alloy molten slurry to the support layer is 0.1T / 10mm to 2T / 10mm;

[0046] (2) mixing a lithium salt, a solvent, and a polymer to obtain a gel electrolyte; coating the gel electrolyte on the surface of the lithium replenishing layer to form a gel electrolyte layer, thereby obtaining a lithium replenishing composite layer.

[0047] Exemplarily, P1 may be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P11 may be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P12 can be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P13 can be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values.

[0048] In the present application, the lithium alloy foil may include but is not limited to lithium aluminum alloy, and the lithium alloy in the lithium alloy molten slurry may include but is not limited to lithium aluminum alloy. In the above step (2), the present application has no special restrictions on the mixing method of lithium salt, solvent, and polymer, as long as the purpose of the present application can be achieved. For example, the polymer can be dissolved in the solvent, and then the lithium salt is added and mixed evenly to obtain a gel electrolyte. The present application has no special restrictions on the coating method of the gel electrolyte on the surface of the lithium replenishing layer, as long as the purpose of the present application can be achieved. For example, the gel electrolyte can be coated on the surface of the lithium replenishing layer by screen printing, extrusion coating, transfer coating or scraping.

[0049] The lithium-replenishing composite layer is prepared by the preparation method of the lithium-replenishing composite layer provided in the present application. The lithium-replenishing composite layer includes a gel electrolyte layer, a lithium-replenishing layer and a supporting layer arranged in a stacked manner. The composition of the gel electrolyte layer and the type of the lithium-replenishing layer are within the scope of the present application. The gel electrolyte layer has a suitable ionic conductivity. The gel electrolyte layer in the lithium-replenishing composite layer contacts the negative electrode material layer. The lithium-replenishing layer and the negative electrode material layer form an internal short circuit. The lithium atoms in the lithium-replenishing layer undergo an oxidation reaction to lose electrons to generate lithium ions. The electrons and lithium ions are transferred to the surface or the inside of the negative electrode material layer through the gel electrolyte layer. The electrons and lithium ions undergo a reduction reaction in the negative electrode material layer to form a lithium-insertion compound, thereby realizing the pre-lithiation process of the negative electrode material layer. Since a gel electrolyte layer is provided between the lithium-replenishing layer and the negative electrode material layer, the possibility of introducing impurities into the lithium-replenishing layer is small. In addition, the above-mentioned pre-lithiation process can quickly replenish lithium and increase the amount of lithium replenishment. At the same time, the interface bonding pressure, bonding time, and bonding temperature are controlled to achieve controllable lithium replenishment, which can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. The support layer can provide better support for the lithium replenishment layer and the gel electrolyte layer, and improve the mechanical strength of the lithium replenishment composite layer, so that the lithium replenishment composite layer can be peeled off from the surface of the negative electrode material layer more smoothly after lithium replenishment, reducing the possibility of fracture of the lithium replenishment composite layer, which is beneficial to the lithium replenishment of the negative electrode plate.

[0050] In one embodiment of the present application, the concentration C of the lithium salt in the gel electrolyte is Li 0.2mol / L to 2mol / L; Based on the mass of the gel electrolyte layer, the mass percentage of the polymer W P 1% to 30%. Li The value of can be 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2 or a range consisting of any two of the above values; W PThe value of can be 1%, 3%, 5%, 7%, 10%, 13%, 15%, 17%, 20%, 23%, 25%, 27%, 30% or a range consisting of any two of the above values. The concentration of lithium salt will affect the ionic conductivity of the gel electrolyte layer, and thus affect the lithium replenishment rate and the amount of lithium replenishment. By regulating the concentration of lithium salt and the mass percentage of the polymer within the scope of this application, it is beneficial to obtain an electrolyte system with excellent mechanical properties, high ionic conductivity and good compatibility, and the gel electrolyte layer can have a suitable ionic conductivity, and electrons and lithium ions can be transferred to the surface or interior of the negative electrode material layer more quickly through the gel electrolyte layer, so that lithium replenishment can be carried out more quickly and the amount of lithium replenishment can be further increased, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery. The present application does not particularly limit the method of regulating the concentration of lithium salt, as long as the purpose of this application can be achieved. For example, the concentration of lithium salt can be regulated by regulating the amount of lithium salt added. Exemplarily, as the amount of lithium salt added increases, the concentration of lithium salt increases; as the amount of lithium salt added decreases, the concentration of lithium salt decreases. The present application has no particular restrictions on the manner of regulating the mass percentage of the polymer, as long as the purpose of the present application can be achieved. For example, the mass percentage of the polymer can be regulated by regulating the amount of polymer added. Exemplarily, when other conditions remain unchanged, as the amount of polymer added increases, the mass percentage of the polymer increases; as the amount of polymer added decreases, the mass percentage of the polymer decreases.

[0051] In one embodiment of the present application, the viscosity η of the gel electrolyte is 30000 mPa·s to 200000 mPa·s. Exemplarily, the value of η can be 30000, 40000, 50000, 60000, 70000, 80000, 90000, 100000, 130000, 150000, 170000, 190000, 200000 or a range consisting of any two of the above values. By regulating the viscosity of the gel electrolyte within the scope of the present application, the gel electrolyte has a suitable viscosity, which is conducive to coating the gel electrolyte on the surface of the lithium replenishment layer, which is conducive to processing performance.

[0052] The third aspect of the present application provides a lithium supplementation method, which comprises the following steps:

[0053] The negative electrode plate is dried until the water content is ≤500ppm, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. It is understood that the above-mentioned negative electrode plate refers to a negative electrode plate that has not been pre-lithiated. Under the conditions of ambient temperature of 25°C to 180°C and humidity ≤1.7%, the lithium-supplementing composite layer prepared by the preparation method in any of the above embodiments and the negative electrode plate are laminated so that the gel electrolyte layer is in contact with the negative electrode material layer, and a pre-lithiation treatment is performed. The lamination pressure P2 of the gel electrolyte layer and the negative electrode material layer is 0.1MPa to 0.6MPa, the lamination time t2 of the gel electrolyte layer and the negative electrode material layer is 0.01h to 1h, and the lamination temperature T2 of the gel electrolyte layer and the negative electrode material layer is 25°C to 90°C. After the pre-lithiation treatment is completed, the lithium-supplementing composite layer and the negative electrode plate are peeled off to form a pre-lithiated negative electrode plate.

[0054] The present application has no particular restrictions on the manner in which the lithium-replenishing composite layer and the negative electrode sheet are bonded, as long as the purpose of the present application can be achieved. For example, the lithium-replenishing composite layer and the negative electrode sheet can be bonded by winding into a roll or pressing into a sheet. The present application has no particular restrictions on the method for regulating the bonding pressure, as long as the purpose of the present application can be achieved. For example, when the lithium-replenishing composite layer and the negative electrode sheet are wound into a roll, the bonding pressure between the gel electrolyte layer and the negative electrode material layer can be regulated by regulating the winding tension. For example, when the lithium-replenishing composite layer and the negative electrode sheet are pressed into a sheet, the bonding pressure between the gel electrolyte layer and the negative electrode material layer can be regulated by regulating the pressing pressure.

[0055] For example, P2 can be 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, or a range consisting of any two of the above values. t2 can be 0.01h, 0.05h, 0.1h, 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, or a range consisting of any two of the above values. T2 can be 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, or a range consisting of any two of the above values.

[0056] In the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0057] In the present application, the negative electrode material layer includes a negative electrode active material. The negative electrode active material includes at least one of a graphite material, hard carbon, a silicon-carbon material or a silicon-oxygen material. The above-mentioned graphite material includes at least one of artificial graphite or natural graphite. In the present application, the silicon-carbon material is a silicon-carbon composite material, and based on the mass of the silicon-carbon composite material, the mass percentage of the silicon element is 30% to 70%, and the mass percentage of the carbon element is 30% to 70%. The present application has no particular restrictions on the silicon-carbon composite material, as long as the purpose of the present application can be achieved. For example, the silicon-carbon composite material can be a composite material obtained by deposition. Exemplarily, the silicon-carbon composite material can be a silicon material deposited on a carbon skeleton, or a carbon material deposited on a silicon skeleton. The silicon-oxygen material includes SiOx, wherein 0<x<2. Exemplarily, the silicon-oxygen material can include silicon oxide (SiO, the molar ratio of silicon to oxygen is 1:1). The negative electrode material layer also includes a negative electrode binder and a negative electrode conductor. The present application has no particular restrictions on the type of negative electrode binder, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include at least one of polyacrylate, polyimide, polyamide, polyamideimide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene butadiene rubber, SBR), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, lithium carboxymethyl cellulose, lithium polyacrylate, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The present application has no particular restrictions on the type of negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent may include but is not limited to at least one of conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. The above-mentioned conductive carbon black may include but is not limited to at least one of Super P, acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or few-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to at least one of vapor-grown carbon fibers (VGCF) or nanocarbon fibers. The above-mentioned metal material may include but is not limited to metal powder and / or metal fiber. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application has no particular restrictions on the mass ratio of the negative electrode active material, the negative electrode binder, and the negative electrode conductive agent in the negative electrode material layer. Those skilled in the art can select according to actual needs as long as the purpose of the present application can be achieved.

[0058] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector (such as a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.), etc.

[0059] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 4 μm to 20 μm. The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided negative electrode material layer is 30 μm to 250 μm.

[0060] The lithium replenishment method provided in the present application is used to prepare a pre-lithiated negative electrode plate, which is beneficial to quickly replenish lithium to the negative electrode plate and increase the amount of lithium replenished in the negative electrode plate. The obtained pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0061] The fourth aspect of the present application provides a pre-lithiated negative electrode plate, which is obtained by the lithium supplementation method in any of the above embodiments. The pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0062] The fifth aspect of the present application provides a secondary battery, the secondary battery comprising the pre-lithiated negative electrode plate in any of the above embodiments. Therefore, the secondary battery of the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.

[0063] In the present application, the secondary battery also includes a positive electrode plate. The positive electrode plate includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along its own thickness direction, or on two surfaces of the positive electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the positive electrode collector or a partial area of ​​the positive electrode collector. This application is not particularly limited as long as the purpose of this application can be achieved.

[0064] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).

[0065] The positive electrode material layer of the present application includes a positive electrode active material, and the positive electrode active material includes a substance that can reversibly embed and extract active ions such as lithium ions. The positive electrode material layer can be one layer or more layers, and each layer in the multi-layer positive electrode material layer can contain the same or different positive electrode active materials. The present application has no special restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. At least one of the above-mentioned lithium nickel cobalt manganese oxide may include LiNi 0.95 Co 0.03 Mn 0.02 O2(Ni95),LiNi 0.91 Co 0.03 Mn 0.06 O2(Ni91), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523) or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 At least one of O2 (NCM111). The positive electrode material layer of the present application also includes a positive electrode conductor and a positive electrode binder. The present application has no special restrictions on the positive electrode conductor and the positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor in the positive electrode material layer may include at least one of the above-mentioned negative electrode conductors; the positive electrode binder in the positive electrode material layer may include at least one of the above-mentioned negative electrode binders. The present application has no special restrictions on the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0066] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode current collector is 6 μm to 25 μm. The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided positive electrode material layer is 25 μm to 250 μm.

[0067] In the present application, the secondary battery also includes an electrolyte. The electrolyte includes a first lithium salt. The present application has no particular restrictions on the type of the first lithium salt, and lithium salts known in the art can be used. For example, the first lithium salt may include but is not limited to lithium hexafluorophosphate, lithium trifluoromethanesulfonyl imide (LiN (CF3SO2) 2, LiTFSI), lithium bis (fluorosulfonyl) imide (Li (N (SO2F) 2), LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis oxalate borate (LiB (C2O4) 2, LiBOB) or lithium difluoro oxalate borate (LiBF2 (C2O4), LiDFOB). The present application has no particular restrictions on the mass percentage of the first lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The electrolyte also includes a non-aqueous organic solvent. The present application has no particular restrictions on the non-aqueous organic solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous organic solvent may include at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), vinylene carbonate, propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned fluorinated carbonate compound may include but is not limited to fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include, but are not limited to, at least one of 1,3-propanesultone, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester.The present application has no particular limitation on the mass percentage of the non-aqueous organic solvent in the electrolyte, as long as the purpose of the present application can be achieved.

[0068] In the present application, the secondary battery also includes a diaphragm. The diaphragm is used to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0069] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a diaphragm binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned diaphragm binder, for example, it may be at least one of the aforementioned negative electrode binders. The polymer layer contains a first polymer, and the material of the first polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or vinylidene fluoride-hexafluoropropylene copolymer.

[0070] The secondary battery of the present application also includes a packaging bag for containing a positive electrode plate, a separator, a pre-lithiated negative electrode plate and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.

[0071] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0072] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no special restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the pre-lithiated negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode sheet, the separator and the pre-lithiated negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection components, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0073] The sixth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.

[0074] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0075] Example

[0076] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0077] Test methods and equipment:

[0078] Ionic conductivity test of gel electrolyte layer:

[0079] (1) A gel electrolyte is applied to the surface of a mold and peeled off to obtain a 40 mm × 40 mm gel electrolyte layer sample.

[0080] (2) The gel electrolyte layer sample is sandwiched between two platinum electrodes to ensure good contact between the gel electrolyte layer sample and the platinum electrodes.

[0081] (3) Using an electrochemical workstation, connect the gel electrolyte layer sample and the platinum electrode to a battery fixture, and set the electrochemical impedance spectroscopy (EIS) test parameters with a frequency range of 1 MHz to 1 Hz and an AC voltage amplitude of 5 mV.

[0082] (4) Perform EIS test at room temperature and record impedance data at different frequencies.

[0083] (5) The impedance data was fitted using the Randles equivalent circuit model, and the resistance R of the gel electrolyte layer sample was obtained from the fitting results. b , and the ionic conductivity σ is calculated according to the following formula:

[0084] σ=Ln / (R b ×a); where Ln is the thickness of the gel electrolyte layer sample and a is the cross-sectional area of ​​the gel electrolyte layer sample.

[0085] Viscosity test of gel electrolyte:

[0086] (1) Use a rotational viscometer to test the viscosity of the gel electrolyte, select a suitable spindle, and select different spindle models according to the viscosity range of the gel electrolyte.

[0087] (2) The polymer is dissolved in a solvent, and then a lithium salt is added and mixed uniformly to obtain a gel electrolyte.

[0088] (3) Pour the gel electrolyte into the sample cup of the rotational viscometer so that the volume of the gel electrolyte covers the working area of ​​the rotor.

[0089] (4) At room temperature, select an appropriate speed (RPM), start the rotational viscometer, and record the viscosity value.

[0090] Thickness test of support layer, lithium supplement layer and gel electrolyte layer:

[0091] Place the sample to be tested on the table, level it, and measure its thickness data as required. Use non-woven fabric to wipe the measuring end face of the micrometer; press the measuring linkage mechanism to make the two measuring end faces completely contact, and press the "zero" key; the two measuring end faces of the micrometer are in contact with the end face of the sample to be tested, read the displayed data, and record the readings. Measure at intervals of 70mm perpendicular to the tape running direction (ie TD direction), and at intervals of 100mm along the tape running direction (ie MD direction); test 12 points along the TD direction of the sample to be tested; test 12 points along the MD direction of the sample to be tested; test a total of 24 points; take the average value of the thickness of the 24 points as the thickness of the sample to be tested.

[0092] The support layer is used as the sample to be tested, and the thickness H3 of the support layer is obtained.

[0093] The support layer and the lithium supplement layer are combined as the sample to be tested, and the total thickness H of the support layer and the lithium supplement layer is obtained. 支撑层&补锂 Layer; the total thickness of the support layer and the lithium supplement layer H 支撑层&补锂层 The difference between the thickness H3 of the support layer and the thickness H2 of the lithium supplement layer is H2, that is, H2 = H 支撑层&补锂层 -H3.

[0094] The support layer, lithium supplement layer and gel electrolyte layer are composited as the sample to be tested, and the total thickness H of the support layer, lithium supplement layer and gel electrolyte layer is obtained. 支撑层&补锂层&凝胶态电解质层 , the thickness of the gel electrolyte layer is H1, that is, H1 = H 支撑层&补锂层&凝胶态电解质层 -H 支撑层&补锂层 .

[0095] Tensile strength test of support layer:

[0096] The steps for testing the tensile strength in the MD direction are as follows: the support layer is cut into standard test strips (width W = 16 mm, length L = 150 mm), wherein the width W of the standard test strip is perpendicular to the running direction of the lithium-replenishing composite layer (i.e., TD direction), and the length L is along the MD direction. Use a tensile testing machine (model instron 3365), clamp both ends of the standard test strip in the upper and lower clamps of the tensile testing machine, so that the standard test strip is centered without folding or twisting, apply tension at a constant speed of 50 mm / min until the standard test strip breaks, and record the load and corresponding extension. Calculate the tensile strength according to the following formula:

[0097] Tensile strength = F / W; where F is the maximum load and W is the width of the standard test specimen.

[0098] Lithium supplement test:

[0099] Use a 1 / 100,000 analytical balance to weigh the mass of the negative electrode before and after lithium replenishment. The area of ​​the negative electrode is 1540.25mm 2The ratio of the mass of the negative electrode sheet before lithium replenishment to the area of ​​the negative electrode sheet is the surface density before lithium replenishment. The ratio of the mass of the negative electrode sheet after lithium replenishment to the area of ​​the negative electrode sheet is the surface density after lithium replenishment. The amount of lithium replenishment is the difference between the surface density after lithium replenishment and the surface density before lithium replenishment. Take 24 groups of negative electrode sheets for measurement and calculate the average value to obtain the amount of lithium replenishment.

[0100] First coulombic efficiency test:

[0101] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: charge the lithium-ion battery in the embodiment or comparative example at 25°C at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, stand for 5 minutes, and then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V. The capacity of the above charging process is recorded as C0, and the capacity of the above discharging process is recorded as C1. The first coulomb efficiency is calculated according to the following formula.

[0102] First coulombic efficiency (%) = C1 / C0×100%.

[0103] Cycle performance test:

[0104] The voltage range marked on the factory battery packaging shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, the lithium-ion battery in the embodiment or comparative example is charged and discharged for the first time, charged at a constant current of 0.2C to a cut-off voltage of 4.45V, and then charged at a constant voltage of 4.45V until the current is less than 0.05C, and after standing for 5 minutes, discharged at a constant current of 0.2C to a cut-off voltage of 3.0V, and the discharge capacity of the lithium-ion battery is measured to be A; then, 400 charging and discharging cycles are performed according to the above steps in an environment of 25°C, and the discharge capacity of the lithium-ion battery at the 400th time is measured to be B, and the cycle capacity retention rate is calculated according to the following formula.

[0105] Cycle capacity retention rate (%) = B / A × 100%.

[0106] The larger the value of the cycle capacity retention rate obtained from the test, the better the cycle performance of the lithium-ion battery.

[0107] Energy density test:

[0108] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, charge the lithium-ion battery in the embodiment or comparative example at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, let it stand for 5 minutes, then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V, and let it stand for 5 minutes. The energy of the above discharge process is recorded as the discharge energy E. Calculate the volume V (mm) of the lithium-ion battery 3 ) = length × width × height.

[0109] Energy density (Wh / L) = E / V × 10 6 .

[0110] Example 1-1

[0111] <Preparation of lithium-supplementing composite layer>

[0112] Under the conditions of ambient temperature of 25°C and humidity of 1.0%, the lithium foil was rolled into a copper foil support layer with a thickness of 14 μm to form a lithium supplement layer. The roller pressure P12 was 1.5T / 10mm to obtain a lithium supplement layer / support layer composite structure.

[0113] Under the conditions of ambient temperature of 25°C and humidity of 1.0%, the polymer polyvinylidene fluoride is dissolved in a solvent, and then lithium salt LiPF6 is added and mixed evenly to obtain a gel electrolyte, and the viscosity η of the gel electrolyte is 100000 mPa·s; the gel electrolyte is coated on the surface of the lithium supplement layer to form a gel electrolyte layer, and the surface density CW of the gel electrolyte layer is 20 g / m 2 , a lithium-replenishing composite layer is obtained. The solvent includes EC and DMC, based on the total volume of the solvent, the volume percentage of EC is 50%, and the volume percentage of DMC is 50%; based on the mass of the gel electrolyte layer, the mass percentage of the polymer is W P is 15%; the concentration of lithium salt in the gel electrolyte C Li The ionic conductivity of the gel electrolyte layer is 1 mol / L. The thickness of the gel electrolyte layer H1 is 10 μm, and the thickness of the lithium supplement layer H2 is 0.03 mm. Along the running direction of the lithium supplement composite layer, the tensile strength K3 of the support layer is 72 N / 10 mm.

[0114] <Preparation of negative electrode sheet>

[0115] The negative electrode active material silicon carbon material, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber (SBR), and the negative electrode binder lithium carboxymethyl cellulose are mixed in a weight ratio of 85:5:5:5, and deionized water is added as the negative electrode solvent, and the mixture is stirred and mixed to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 28wt%; the negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 90°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. Dry under vacuum conditions at 90°C for 1h, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 51mm×44.2mm is obtained. Among them, the silicon-carbon material is a silicon-carbon composite material, and based on the mass of the silicon-carbon composite material, the mass percentage of silicon element is 50%, and the mass percentage of carbon element is 50%; the surface density of the negative electrode material layer is 2.3mg / cm 2 The compaction density of the cold pressing process is 1.0g / cm 3 .

[0116] <Preparation of pre-lithiated negative electrode sheet>

[0117] The prepared negative electrode plate is dried until the water content is ≤500ppm; under the conditions of ambient temperature of 25°C and humidity of 1.0%, the prepared lithium supplement composite layer and the prepared negative electrode plate are laminated so that the gel electrolyte layer is in contact with the negative electrode material layer, the lamination method is pressing into sheets, and pre-lithiation treatment is performed, the lamination pressure P2 of the gel electrolyte layer and the negative electrode material layer is 0.3MPa, the lamination time t2 of the gel electrolyte layer and the negative electrode material layer is 0.5h, and the lamination temperature T2 of the gel electrolyte layer and the negative electrode material layer is 50°C. After the pre-lithiation treatment is completed, the lithium supplement composite layer and the negative electrode plate are peeled off to form a pre-lithiation negative electrode plate.

[0118] <Preparation of positive electrode sheet>

[0119] The positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode conductive agent acetylene black, and the positive electrode binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as the positive electrode solvent, and the mixture is stirred and mixed to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 110°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 110°C for 1h, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 48mm×41.2mm is obtained. Among them, the surface density of the positive electrode material layer is 19.0mg / cm2 The compaction density of the cold pressing process is 4.15g / cm 3 .

[0120] <Preparation of Electrolyte>

[0121] In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and ethyl propionate (EP) are mixed in a weight ratio of 3:1:3:3 to obtain a base solvent, and then a first lithium salt, lithium hexafluorophosphate (LiPF6), is added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of the first lithium salt LiPF6 is 12.5%, and the remainder is the base solvent.

[0122] <Preparation of Separator>

[0123] A porous polypropylene film with a thickness of 5 μm (provided by Celgard Company) was used as a separator.

[0124] <Preparation of lithium-ion batteries>

[0125] The prepared positive electrode sheet, separator, pre-lithiated negative electrode sheet and separator are stacked in order, so that the separator is placed between the positive electrode sheet and the pre-lithiated negative electrode sheet to play an isolating role, and the electrode assembly is wound. After welding the pole ear, the electrode assembly is placed in an aluminum plastic film, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and the electrolyte is injected. After vacuum packaging, standing, formation (charging to 3.5V at a constant current of 0.02C, and then charging to 3.9V at a constant current of 0.1C), degassing, trimming, and capacity processing steps, a lithium-ion battery is obtained.

[0126] Example 1-2 to Example 1-5

[0127] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0128] Examples 1-6

[0129] Except that in <Preparation of lithium-replenishing composite layer>, the lithium-replenishing layer / supporting layer composite structure is obtained by the following method, the rest is the same as Example 1-1.

[0130] Under the conditions of ambient temperature of 25°C and humidity of 1.0%, the lithium metal powder slurry was coated on a copper foil support layer with a thickness of 14 μm, dried, and rolled to form a lithium supplement layer, and the roller pressure P11 was 1.5T / 10mm to obtain a lithium supplement layer / support layer composite structure. The solvent of the lithium metal powder slurry was n-hexane, and the solid content was 30wt%.

[0131] Examples 1-7

[0132] Except that in <Preparation of lithium-replenishing composite layer>, the lithium-replenishing layer / supporting layer composite structure is obtained by the following method, the rest is the same as Example 1-1.

[0133] Under the conditions of ambient temperature of 25°C and humidity of 1.0%, lithium molten slurry was coated on a copper foil support layer with a thickness of 14 μm, cooled and rolled to form a lithium replenishing layer. The roller pressure P13 was 1.5T / 10mm to obtain a lithium replenishing layer / supporting layer composite structure.

[0134] Example 1-8 to Example 1-20

[0135] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0136] Example 1-21 to Example 1-25

[0137] Except for adjusting the amount of lithium salt added so that the concentration of lithium salt is as shown in Table 1, the rest is the same as Example 1-1.

[0138] Example 1-26 to Example 1-31

[0139] The process was the same as Example 1-1 except that the coating amount of the gel electrolyte was adjusted so that the surface density of the gel electrolyte layer was as shown in Table 1.

[0140] Example 1-32 to Example 1-33

[0141] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0142] Example 2-1 to Example 2-10

[0143] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1.

[0144] Comparative Example 1-1

[0145] Except that the gel electrolyte layer is not provided in the preparation of lithium supplementing composite layer, the rest is the same as that of Example 1-1.

[0146] Comparative Example 2-1 to Comparative Example 2-5

[0147] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1.

[0148] The preparation parameters and electrical performance parameters of each embodiment and comparative example are shown in Tables 1 and 2.

[0149]

[0150]

[0151]

[0152] Table 2

[0153]

[0154] It can be seen from Examples 1-1 to 1-33, Comparative Example 1-1, Examples 2-1 to 2-10, and Comparative Example 2-1 to Comparative Example 2-5 that the lithium replenishing composite layer is prepared by the preparation method of the lithium replenishing composite layer provided in the present application, and then the pre-lithiated negative electrode plate is prepared by the lithium replenishing method provided in the present application, and the pre-lithiated negative electrode plate is applied to the lithium ion battery, and the prepared lithium ion battery has a high lithium replenishing amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the lithium ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium ion battery can be improved. In Comparative Example 1-1, the preparation method of the lithium replenishing composite layer is not within the scope of the present application, and the prepared lithium ion battery has a low lithium replenishing amount, first coulombic efficiency, cycle capacity retention rate and energy density. In Comparative Examples 2-1 to 2-5, the lithium replenishing method is not within the scope of the present application, and the prepared lithium ion battery has a low lithium replenishing amount, first coulombic efficiency, cycle capacity retention rate and energy density.

[0155] The type of polymer usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-8 to 1-12 that the type of polymer is within the scope of this application, and the prepared lithium-ion battery has a higher lithium replenishment amount, initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that the initial coulombic efficiency of lithium-ion batteries can be improved, the cycle capacity attenuation can be reduced, and the energy density of lithium-ion batteries can be improved.

[0156] The type of solvent usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-13 and 1-14 that the type of solvent is within the scope of this application, and the prepared lithium-ion battery has a higher lithium replenishment amount, initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that the initial coulombic efficiency of lithium-ion batteries can be improved, the cycle capacity attenuation can be reduced, and the energy density of lithium-ion batteries can be improved.

[0157] The type of lithium salt usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-15 to 1-20 that the type of lithium salt is within the scope of this application, and the prepared lithium-ion battery has a higher lithium supplement amount, initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that the initial coulombic efficiency of lithium-ion batteries can be improved, the cycle capacity attenuation can be reduced, and the energy density of lithium-ion batteries can be improved.

[0158] The concentration of lithium salt usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 1-21 to 1-25 that when the concentration of lithium salt is within the range of this application, the prepared lithium-ion battery has a higher lithium supplement amount, initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that the initial coulombic efficiency of lithium-ion batteries can be improved, the cycle capacity attenuation can be reduced, and the energy density of lithium-ion batteries can be improved.

[0159] The viscosity of the gel electrolyte usually affects the processing performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-8 to 1-25, 1-32, and 1-33 that the viscosity of the gel electrolyte is within the scope of the present application, the lithium-ion battery has good processing performance, and the prepared lithium-ion battery has a high lithium replenishment amount, first coulomb efficiency, cycle capacity retention rate, and energy density, indicating that the first coulomb efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium-ion battery can be improved.

[0160] The surface density of the gel electrolyte layer usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery. It can be seen from Examples 1-1, 1-26 to 1-31 that the surface density of the gel electrolyte layer is within the scope of the present application, and the prepared lithium-ion battery has a higher lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium-ion battery can be improved.

[0161] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements that are inherent to such process, method or article.

[0162] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0163] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A lithium supplement composite layer, wherein: The lithium replenishing composite layer comprises a stacked gel electrolyte layer, a lithium replenishing layer and a supporting layer, wherein the lithium replenishing layer is arranged between the gel electrolyte layer and the supporting layer, the gel electrolyte layer comprises a lithium salt, a solvent and a polymer, and the lithium replenishing layer comprises lithium metal and / or a lithium alloy.

2. The lithium supplement composite layer according to claim 1, wherein: The ion conductivity σ of the gel electrolyte layer is 0.1 mS / cm to 15 mS / cm.

3. The lithium supplement composite layer according to claim 1, wherein: The lithium salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate) or lithium oxalatodifluoroborate.

4. The lithium supplement composite layer according to claim 1, wherein: The solvent includes at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, N,N-dimethylformamide, N-methylpyrrolidone, dioxolane, 1-butyl-3-methylimidazolium bromide or ethylene glycol dimethyl ether.

5. The lithium supplement composite layer according to claim 1, wherein: The polymer includes at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer or polyethylene glycol dimethacrylate.

6. The lithium supplement composite layer according to claim 1, wherein: The surface density CW of the gel electrolyte layer is 1 g / m 2 Up to 100g / m 2 Preferably, the surface density CW of the gel electrolyte layer is 2 g / m 2 Up to 40g / m 2 .

7. A method for preparing the lithium supplement composite layer according to any one of claims 1 to 6, comprising the following steps: (1) coating the support layer with lithium metal powder slurry, drying it, and rolling it to form the lithium supplement layer; or rolling lithium foil and / or lithium alloy foil onto the support layer to form the lithium supplement layer; or coating the support layer with lithium or lithium alloy molten slurry, cooling it, and rolling it to form the lithium supplement layer; wherein the rolling pressure P1 is 0.1T / 10mm to 2T / 10mm; (2) mixing the lithium salt, the solvent and the polymer to obtain a gel electrolyte; coating the gel electrolyte on the surface of the lithium replenishing layer to form the gel electrolyte layer, thereby obtaining the lithium replenishing composite layer.

8. The preparation method according to claim 7, wherein: The concentration of lithium salt in the gel electrolyte is C Li 0.2 mol / L to 2 mol / L; based on the mass of the gel electrolyte layer, the mass percentage of the polymer W P 1% to 30%.

9. The preparation method according to claim 7, wherein: The viscosity η of the gel electrolyte is 30000 mPa·s to 200000 mPa·s.

10. A lithium supplementation method comprising the following steps: Drying a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; The lithium-replenishing composite layer prepared by the preparation method described in any one of claims 7 to 9 and the negative electrode plate are laminated so that the gel electrolyte layer contacts the negative electrode material layer, and a pre-lithiation treatment is performed. The lamination pressure P2 of the gel electrolyte layer and the negative electrode material layer is 0.1 MPa to 0.6 MPa, the lamination time t2 of the gel electrolyte layer and the negative electrode material layer is 0.01 h to 1 h, and the lamination temperature T2 of the gel electrolyte layer and the negative electrode material layer is 25°C to 90°C. After the pre-lithiation treatment is completed, the lithium-replenishing composite layer and the negative electrode plate are peeled off to form a pre-lithiation negative electrode plate.

11. A pre-lithiated negative electrode plate, wherein: The pre-lithiated negative electrode plate is obtained by the lithium replenishment method according to claim 10.

12. A secondary battery, wherein: The secondary battery comprises the pre-lithiated negative electrode sheet according to claim 11. 13 . An electronic device comprising the secondary battery according to claim 12 .

Citation Information

Cited By

  • Recyclable pre-lithiation composite membrane, pre-lithiation negative pole piece based on pre-lithiation composite membrane and preparation method and application of pre-lithiation negative pole piece

    CN121307033A